The effects of raddiation on the optical properties of GERMANIUM SELENIDE semiconductor. - Baghdad Science Journal (مجلة بغداد للعلوم)
Study was made on the optical properties of Ge2oSe8othinfilms prepared by vac-uum evaporation as radiated by (0,34,69) Gy of 13 ray.The optical band gab Eg and tailing band A.Et were studied in the photon energy range ( 1 to 3)eV. The a-Ge20Se8o film was found to be indirect gap with energy gap of (1.965,1.9 , 1.82) eV at radiated by B ray with absorption doses of (0,34,69)Gy respectively.The Ea and AEt of Ge20Se80 films showed adecrease in E8 and an increase in AEt with radiation. This be-havior may be related to structural defects and dangling bonds.